Artifacts and Pitfalls in Myocardial Perfusion Imaging - Burrell, Steven; MacDonald, Anita (Journal of nuclear medicine technology, 2006)
Myocardial perfusion imaging (MPI) is an important imaging modality in the management of patients with cardiovascular disease. MPI plays a key role in diagnosing cardiovascular disease, establishing prognosis, assessing the effectiveness of therapy, and evaluating viability. However, MPI is a complex process, subject to a variety of artifacts and pitfalls, which may limit its clinical utility. These factors may be related to the patient (including unique aspects of the patient's heart), the nuclear medicine equipment, or the actions of the technologist. After reviewing this article, the reader should be familiar with the causes and the effects of these potential artifacts and pitfalls. The reader should develop an understanding of steps to limit these factors, actions to correct them if they do arise and, when necessary, how to incorporate their influence into the interpretation of the study.